B4 suppresses lymphoma progression by inhibiting fibroblast growth factor binding protein 1 through intrinsic apoptosis - Krishnapriya M. Varier; Krishnapriya M. Varier; Gou Dan; Xiaolong Li; Wuling Liu; Wuling Liu; Fei Jiang; Ke-Gang Linghu; Yanmei Li; Yanmei Li; Yaacov Ben-David; Yaacov Ben-David; et al. (Frontiers Media S.A., 2024)
Lymphoma positions as the fifth most common cancer, in the world, reporting remarkable deaths every year. Several promising strategies to counter this disease recently include utilizing small molecules that specifically target the lymphoma cellular proteins to overwhelm its progression. FGFBP1 is a soluble intracellular protein that progresses cancer cell proliferation and is upregulated in several cancers. Therefore, inhibiting FGFBP1 could significantly slow down lymphoma progression through triggering apoptosis. Thus, in this study, a flavonoid B4, isolated from Cajanus cajan, has been investigated for its effects of B4 on lymphoma, specifically as an FGFBP1 inhibitor. B4 could selectively hinder the growth of lymphoma cells by inducing caspase-dependent intrinsic apoptosis through G1/S transition phase cell cycle arrest. RNA sequencing analysis revealed that B4 regulates the genes involved in B-cell proliferation and DNA replication by inhibiting FGFBP1 in vitro. B4 increases the survival rate of lymphoma mice. B4 also represses the growth of patient-derived primary lymphoma cells through FGFBP1 inhibition. Drug affinity responsive target stability experimentations authorize that B4 powerfully binds to FGFBP1. The overexpression of FGFBP1 raises the pharmacological sensitivity of B4, supplementing its specific action on lymphoma cells. This study pioneers the estimation of B4 as a possible anticancer agent for lymphoma treatment. These outcomes highlight its selective inhibitory effects on lymphoma cell growth by downregulating FGFBP1 expression through intrinsic apoptosis, causing mitochondrial and DNA damage, ultimately leading to the inhibition of lymphoma progression. These suggest B4 may be a novel FGFBP1 inhibitor for the lymphoma treatment.